2020
DOI: 10.37745/ejaafr/vol8.no7.pp97-120.2020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Cost on Performances of Quoted Firms in Sub-Saharan Africa, 2007-2016

Abstract: The study examined the effect of environmental costs on performances of quoted firms in Sub Saharan Africa. The study adopted longitudinal/panel ex-post facto research design and random sampling technique while quantitative secondary data covering 2007 to 2016 were obtained for sixty-four extractive and industrial firms quoted in the Stock Exchanges of four Sub-Sahara African countries namely South Africa, Nigeria, Ghana and Tanzania. The models for the study were estimated using Ordinary least square regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Some earlier studies, such as those by Cormier and Magnan (2007), Deswanto & Siregar (2018), and Nwaimo (2020), and Rashid & Hossain (2022 found no linkage between environmental disclosure and corporate financial outcomes. Egbunike and Okoro (2018) also examined the profitability impact of green accounting measured by costs associated with social, environmental, health, and safety risks.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 82%
“…Some earlier studies, such as those by Cormier and Magnan (2007), Deswanto & Siregar (2018), and Nwaimo (2020), and Rashid & Hossain (2022 found no linkage between environmental disclosure and corporate financial outcomes. Egbunike and Okoro (2018) also examined the profitability impact of green accounting measured by costs associated with social, environmental, health, and safety risks.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 82%
“…Accounting systems such as carbon accounting systems can assist companies in managing and reducing carbon emissions. It is because investors value companies that use modern technology and approaches to reducing environmental impacts (Nwaimo, 2020). In addition, properly managing environmental costs empowers a firm to achieve operational efficiency, leading to cost savings and increased competitive advantage (Adediran et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The authors stressed that lessening environmental costs is associated with positive company performance. Numerous studies have been carried out to determine the effect of environmental costs on financial performance, all establishing that further research is critical (Nwaimo, 2020;Onyinyichi et al, 2017;Lee, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the long run, strategic investments in environmental restoration can contribute to improved financial performance by mitigating operational risks, enhancing corporate reputation, and reducing regulatory scrutiny. Studies like those conducted by Nwaimo (2020) and Anselm and Janefrances (2020) have shown varying perspectives on the impact of restoration costs on financial performance, suggesting the need for careful management and evaluation of these expenditures to achieve optimal outcomes.…”
Section: Environmental Restoration Cost and Financial Performance (Pa...mentioning
confidence: 99%